2010
DOI: 10.1016/j.aquatox.2010.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen responses in killifish (Fundulus heteroclitus) from polluted and unpolluted environments are site- and gene-specific

Abstract: Epidemiological, ecological, and laboratory-based studies support the hypothesis that endocrine disrupting chemicals (EDCs) in the environment are responsible for developmental and reproductive abnormalities. We have previously described a killifish population resident in a highly polluted Superfund site (New Bedford Harbor, NBH) that shows evidence of exposure to an estrogenic environment and endocrine disruption. Here, we compare NBH with a local reference population (Scorton Creek, SC) for developmental pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 62 publications
4
24
1
Order By: Relevance
“…Female killifish from New Bedford Harbor, similar to those from Newark Bay, exhibit decreased vitellogenin expression (mRNA and protein), decreased gonadal somatic index, and decreased circulating 17β-estradiol levels (Greytak et al ., 2005). Challenge studies with 17β-estradiol demonstrated that larval killifish from New Bedford Harbor have a shifted dose-response for ER α expression, but exhibit normal vitellogenin inducibility (Greytak et al ., 2010). The relevance of these impacts to the formation of eggs and reproductive success of females at New Bedford Harbor are not clear because fecundity has been shown to be normal and not impacted (Black et al ., 1998).…”
Section: 0 Discussionmentioning
confidence: 99%
“…Female killifish from New Bedford Harbor, similar to those from Newark Bay, exhibit decreased vitellogenin expression (mRNA and protein), decreased gonadal somatic index, and decreased circulating 17β-estradiol levels (Greytak et al ., 2005). Challenge studies with 17β-estradiol demonstrated that larval killifish from New Bedford Harbor have a shifted dose-response for ER α expression, but exhibit normal vitellogenin inducibility (Greytak et al ., 2010). The relevance of these impacts to the formation of eggs and reproductive success of females at New Bedford Harbor are not clear because fecundity has been shown to be normal and not impacted (Black et al ., 1998).…”
Section: 0 Discussionmentioning
confidence: 99%
“…In addition, Atlantic Wood offspring were more susceptible to mortality associated with infectious disease (Frederick, Van Veld, & Rice, 2007), to toxicity associated with photoactivation of PAHs, and to acute hypoxia (Meyer & Di Giulio, 2003), although they were less susceptible to the model pro‐oxidant tert ‐butyl hydroperoxide than reference fish (Meyer, Smith, Winston, & Di Giulio, 2003). Altered estrogen signaling has been observed in DLC‐tolerant killifish from both Newark and NBH (Bugel et al., 2011, 2014; Greytak & Callard, 2007; Greytak et al., 2010). NBH killifish are more sensitive to the pro‐oxidant chemical tert ‐butylhydroquinone as compared to fish from a reference site (Harbeitner, Hahn, & Timme‐Laragy, 2013); however, the opposite effect was seen in ER fish, which were more tolerant of the oxidant tert ‐butylhydroperoxide than reference fish (Meyer et al., 2003).…”
Section: Ecological Considerationsmentioning
confidence: 99%
“…Our findings may indicate that individuals differ in their sensitivity to EE2 exposure. For example, greater interindividual variability in estrogen response is found in killifish populations in polluted areas than that in other areas (Greytak et al 2010), and the mechanisms underlying within-and between-population variation in sensitivity to pollutants should be explored further. It is also possible that the behavioral differences prevalent within populations may in part result from differential exposure to EDCs (Breckels and Neff 2010) and future studies should examine the degree of variation found in populations of threespine stickleback from a range of areas that differ in the amount and types of contaminants present.…”
Section: Discussionmentioning
confidence: 98%